2008
DOI: 10.1007/s10038-008-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of ABCG8:D19H gene polymorphism with hypercholesterolemia and insulin resistance

Abstract: The absorption efficiency of cholesterol is closely correlated to dietary phytosterol content and determined by genetic factors. The ATP-binding cassette (ABC) transporters ABCG5 and ABCG8 act as a sterol efflux pump to regulate the absorption of cholesterol and phytosterol. The levels of cholesterol and phytosterol associated with a Chinese diet are very different from those associated with a Western diet. This study aims to explore the association between serum total cholesterol/LDL-C levels and ABCG5/ABCG8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…15 ). Several studies showed positive associations with plasma lipoprotein levels ( 5,7,8 ), which we and others were not able to replicate. The majority of these studies were small-scaled.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…15 ). Several studies showed positive associations with plasma lipoprotein levels ( 5,7,8 ), which we and others were not able to replicate. The majority of these studies were small-scaled.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, due to their skewed distribution, triglyceride data could not be pooled. Twelve studies reported signifi cant associations with baseline triglyceride levels, which mostly involved the p.T400K polymorphism ( 13,29,33 ); however, this was not consistent throughout all included studies ( 8,11,12,27,(30)(31)(32). Finally, in our analyses, we assumed a dominant genetic model, as most of the included studies presented their data according to this model.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The D19H polymorphism has been positively associated with the risk of cholesterol gallstones in three independent studies using multiple ethnicities [24-26]. In a few studies, plasma levels of plant sterols were inversely related to BMI and markers of insulin resistance [27]. However, phytosterol supplementation had no beneficial effect on the development of obesity and insulin resistance in a high-fat diet model of obesity in mice [28].…”
Section: Introductionmentioning
confidence: 99%